THE VARIETY OF FACTORS THAT INFLUENCE THE BIOMECHANICAL PROPERTIES OF THE LIMB SKIN DURING LENGTHENING - Grebeniuk, L.A.; Popkov, A.V.; Shchurov, V.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The aim of this work is to analyze the influence of some factors on biomechanical behavior of the human skin in natural growth and in graduated lengthening with application of the Ilizarov fixator. 45 healthy individuals of various age and 104 patients suffering from congenital shortening of one lower limb or osteomyelitic sequelae have been examined. The limb discrepancy was eliminated by mono- and bilocal osteosynthesis with application of the Ilizarov fixator. The amount of lengthening comprised 3 - 14 cm, its relative value achieved 6 - 30%. Distraction started in 5 days following fixator placement. Biomechanical parametres were determined with the help of the device designed by A.A. Utenkin. The method allows for studying skin deformation properties - shift stiffness (S, kg/mm2) by minimal in time loading but constant in value moment, as well as for calculation of the amount of relative deformation (stretching,., %). The work reports on the effect of different factors – structural and age ones, conditions of reparative lengthening and processes of regeneration – on the mechanical behavior of the limb skin in shortening of different etiology and gradual traction for equalizing limb length. There is a number of factors having influence on the skin biomechanics of the human extremity: 1 structural peculiarities of the collagen bundles and elastic fibres in the papillary and reticular dermis layers (collagenous fibres make up 98% of the connective dermis tissue and provide its high stiffness). The conformation principle of the collagenous and elastic fibrillas and fibres is their spiral character. 2 - the type of the collagen viscosity in the dermis, especially in its deep layers; 3 - age factor; 4 - an amount and etiology of limb shortening in patients with the locomotor system orthopaedic pathology; 5 - the method of limb shape modeling (lengthening and deformity correction) in the conditions of the guided transosseous osteosynthesis (mono- and bilocal osteosynthesis); 6 - skin regeneration (Ilizarov effect) as a consequence of the formogenetic effect appearing in the conditions of tension stress.